Empowerment of Ecotourism Village: Integration of Community Empowerment and Asset-Based Community Development (ABCD) Method - Kamelia, Lia; Sururie, Ramdani Wahyu; Aziz, Rohmanur; Martina, Annisa (LP2M of Institute for Research and Community Services - UIN Walisongo, 2023)
Empowering the community is an endeavor to prepare society for achieving progress, independence, and well-being within a sustainable social justice environment. Effective community empowerment must be tailored to the specific conditions of the target. Correspondingly, the objective of this program was to construct and empower an educational ecotourism village by implementing a hybrid method combining Sisdamas (Community Empowerment System) and Asset-Based Community Development (ABCD). This hybrid approach was expected to facilitate the identification of existing community assets and enhance synergy among stakeholders in creating an educational ecotourism village. Moreover, integrating these two methods could result in an effective, efficient, and sustainable coaching process. Cigugurgirang village possesses several assets that can be developed into an agricultural educational tourism area, including orange gardens, grape vineyards, and ornamental plant areas. They serve as the initial foundation for asset identification. The evaluation of the coaching process incorporated the Social Return on Investment (SROI) framework analysis, yielding a value of 10.16:1. Thus, every investment of 1 million rupiahs would generate a social value of 10.16 million rupiahs. In summary, the present community empowerment program had a multi-faceted impact, encompassing economic, educational, and social benefits. Its primary focus was establishing a sustainable and socially just environment, utilizing a combination of methods to maximize effectiveness. Furthermore, SROI analysis underscored the significant social value generated by the program's investments.